Residents' crime and safety perceptions in gated and non-gated low middle income communities in Kuala Lumpur, Malaysia - Mohit, Mohammad Abdul; Abdulla, Aishath (Kulliyyah of Architecture and Environmental Design, IIUM, 2011)
Property crimes in residential areas has become a concerning issue in Malaysia. Environmental design based crime prevention theories such as Defensible Space, Crime Prevention Through Environmental Design (CPTED) and 2nd generation CPTED recommend to construct gates and fences as target hardening measures in the residential areas to prevent crimes. However, these concepts have generated several issues, including the safe environment they offer. Thus, this paper aims at examining the safety perception of the residents in gated and guarded vis-ii-vis nongated and guarded communities. Two low middle income housing communities - a gated and guarded community (GC) and a non-gated and guarded community (NGC) were chosen for the study. Relationship between residents' crime experiences and perception of safety were studied in both communities and it was found that crime rates are higher in the GC than in the NGC and this indicates that GCs are not safer than NGCs. Based on the findings, the study comes up with several recommendations in order to enhance safety perceptions of low-middle income apartment communities in Kuala Lumpur.